ASSOCIATION OF URINARY TRACT INFECTION WITH PROTEIN CALORIE MALNUTRITION IN PAEDIATRIC POPULATION PRESENTED TO KHYBER TEACHING HOSPITAL - Rahman, Syed Kaleem Ur; Pervez, Sana; Khan, Husna; Afridi, Jan Muhammad; Zeb, Rifaq; Sadiqa, Bibi (Khyber Journal of Medical Sciences, 2024)
Objective: The objective of this study was to determine the prevalence of urinary tract infection (UTI) in children with severe acute malnutrition in the paediatric department of Khyber teaching hospital. Methods: This cross sectional descriptive questionnaire based study was conducted at the Department of Child Health, Khyber Teaching Hospital Peshawar, Pakistan from June 2020 to June 2022.The sample size included 218 patients. 218 urine samples were sent for routine examination and cultures. Nonprobability consecutive sampling technique was used for sample collection. Data was analysed using SPSS version 21.0. Percentages were calculated for categorical variables. Chi square test was applied where needed to measure the association. P value<0.05 was taken as significant. Incidence was calculated in percentages . Results: Total 218 patients were included in the study. Age ranged between 6 months to 5 years. There were total 118(54.1%) male and 100 (45.87%) female. Urine culture test was positive in 44% of females and 25.4% of males. Urine culture was positive in 42% of grade 3 Protein calorie malnutrition (PCM), 27.5% of grade 2 PCM and 17% of grade 1 PCM. The overall prevalence of UTI was 33.9% in PCM. Conclusion: Since UTI is more prevalent in malnourished children. This study is therefore conducted to rule out UTI by means of urine culture in every malnourished child, so adequate treatment is started in time, to prevent further compromise on the child’s nutritional status and to avert further complications of malnutrition and UTI it-self.